THE INFLUENCE OF NARCISSISTIC LEADERSHIP, BURNOUT AND JOB SATISFACTION ON ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) - Malia Nurmaliah; Kabul Wahyu Utomo; Wenda Wahyu Christiyanto (Program Studi Manajemen Dakwah - Fakultas Dakwah dan Ilmu Komunikasi - UIN Syarif Hidayatullah Jakarta, 2026)
This study aims to determine the effect of narcissistic leadership on organizational citizenship behaviour (OCB) mediated by burnout and job satisfaction. This research is a quantitative approach with causality analysis. Data were collected using a questionnaire developed based on a five point Likert scale. Questionnaires were distributed to 305 civil servants of the Directorate General of Islamic Community Guidance Ministry of Religious Affairs of the Republic of Indonesia. A total of 178 questionnaires were returned and deemed eligible for analysis, resulting in a response rate of 58.36%. The data were analyzed using the SEM-PLS method with the help of SmartPLS 4 software. The results showed that narcissistic leadership has a positive and significant effect on OCB and burnout, while having a negative and significant effect on job satisfaction. Burnout has a negative and significant effect on job satisfaction and OCB. Furthermore, job satisfaction has a positive and significant effect on OCB. Burnout partially mediates the relationship between narcissistic leadership and OCB, as well as the relationship between narcissistic leadership and job satisfaction. In addition, job satisfaction partially mediates the relationship between burnout and OCB and the relationship between narcissistic leadership and OCB. Keywords: burnout; job satisfaction; narcissistic leadership; organizational citizenship behaviour